2021
DOI: 10.1029/2020jd034410
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Iodine in Aerosol

Abstract: In this work we describe the compilation and homogenization of an extensive dataset of aerosol iodine field observations in the period between 1963 and 2018 and we discuss the spatial and temporal dependences of total iodine in bulk aerosol by comparing the observations with CAM-Chem model simulations. Total iodine in aerosol shows a distinct latitudinal dependence, with an enhancement towards the northern hemisphere (NH) tropics and lower values towards the poles. This behavior, which has been predicted by at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Yu et al (2019) recently demonstrated that addition of iodide and hydrogen peroxide (H 2 O 2 ) to a lowiodine aerosol sample generated a large number of organic iodine species. Since acoustic cavitation during ultrasonication generates H 2 O 2 and other reactive oxygen species (Kanthale et al, 2008), the result of Yu et al (2019) is further evidence that the use of ultrasonic agitation is likely to alter both inorganic and organic speciation of iodine prior to its determination. This raises the possibility that much of the published literature on I speciation in aerosols over the oceans is potentially unreliable.…”
Section: Introductionmentioning
confidence: 98%
“…Yu et al (2019) recently demonstrated that addition of iodide and hydrogen peroxide (H 2 O 2 ) to a lowiodine aerosol sample generated a large number of organic iodine species. Since acoustic cavitation during ultrasonication generates H 2 O 2 and other reactive oxygen species (Kanthale et al, 2008), the result of Yu et al (2019) is further evidence that the use of ultrasonic agitation is likely to alter both inorganic and organic speciation of iodine prior to its determination. This raises the possibility that much of the published literature on I speciation in aerosols over the oceans is potentially unreliable.…”
Section: Introductionmentioning
confidence: 98%
“…Total soluble iodine (TSI) in aerosols in the MBL is characterised by geographical variability, being latitudinally and longitudinally dependent on global ocean temperature, seawater iodine content, and atmospheric ozone (Gómez Martín et al, 2021). TSI itself consists of iodide (I − ), iodate (IO 3 − ), and soluble organic iodine (SOI).…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol iodine quantities are defined as in Gómez Martín et al. ( 2021 ). TI is given by the sum of total soluble iodine (TSI) and nonsoluble iodine (NSI): TI = TSI + NSI.…”
Section: Methodsmentioning
confidence: 99%
“…We have compiled the available iodine speciation data from cruises and coastal and insular ground‐based stations with the aim of inspecting the spatial variability of the ensemble and comparing them with other global ocean and aerosol variables. For completeness, we also analyze the size distribution of total and soluble iodine, which were not specifically addressed in our previous work (Gómez Martín et al., 2021 ). The questions that we want to address in this work are as follows: which species dominates the soluble iodine speciation at different latitudes and longitudes?…”
Section: Introductionmentioning
confidence: 99%